Asymptomatic uterine incarceration at term: Successful management of a rare complication in pregnancy - Po-Chao Hsu; Mu-Hsien Yu; Chen-Yu Wang; Yu-Kuen Wang; Chun-Kai Wang; Her-Young Su (Elsevier, 2018)
Objective: Incarcerated gravid uterus is a rare complication of pregnancy and can become a critical condition during delivery. For extremely uncommon cases that persist to the third trimester, correct diagnosis before delivery and appropriate management of the associated complications are important. Case report: This was the first case of a full-term pregnancy with incarcerated gravid uterus, reported at a medical center. The condition was not diagnosed during pregnancy, which led to serious complications during the cesarean delivery; however, the prognosis was favorable because of the timely management. Conclusion: Based on the previous case reports and clinical presentation of this case, early diagnosis with ultrasound and pelvic examination is the key to successful treatment. Vertical and more cephalad uterine incision reduces the risk of bladder perforation and injury to the cervix and vagina. A successful teamwork of obstetricians, gynecologists, urologists, and anesthesiologists can ensure favorable outcomes for both mother and fetus. Keywords: Cesarean delivery, Incarcerated gravid uterus, Third trimester